Association between pre-eclampsia and locally derived traffic-related air pollution: a retrospective cohort study. Issue 2 (9th August 2012) - Pereira, Gavin; Haggar, Fatima; Shand, Antonia W; Bower, Carol; Cook, Angus; Nassar, Natasha
Abstract : Background: Pre-eclampsia is a common complication of pregnancy and is a major cause of fetal–maternal mortality and morbidity. Despite a number of plausible mechanisms by which air pollutants might contribute to this process, few studies have investigated the association between pre-eclampsia and traffic emissions, a major contributor to air pollution in urban areas. Objective: The authors investigated the association between traffic-related air pollution and risk of pre-eclampsia in a maternal population in the urban centre of Perth, Western Australia. Method: The authors estimated maternal residential exposure to a marker for traffic-related air pollution (nitrogen dioxide, NO2 ) during pregnancy for 23 452 births using temporally adjusted land-use regression. Logistic regression was used to investigate associations with pre-eclampsia. Results: Each IQR increase in levels of traffic-related air pollution in whole pregnancy and third trimester was associated with a 12% (1%–25%) and 30% (7%–58%) increased risk of pre-eclampsia, respectively. The largest effect sizes were observed for women aged younger than 20 years or 40 years or older, aboriginal women and women with pre-existing and gestational diabetes, for whom an IQR increase in traffic-related air pollution in whole pregnancy was associated with a 34% (5%–72%), 35% (0%–82%) and 53% (7%–219%) increase in risk of pre-eclampsia, respectively. Conclusions: Elevated exposure to traffic-related air pollution in pregnancy was associated with increased risk of pre-eclampsia. Effect sizes were highest for elevated exposures in third trimester and among younger and older women, aboriginal women and women with diabetes.